2016
DOI: 10.1556/066.2016.45.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1-MCP on apricots at different temperatures and days after harvest

Abstract: The effi cacy of 1-MCP on apricots at different treatment temperatures and days after harvest during 6 weeks of storage at 1 °C was investigated. On the 1 st , 3rd , or 5 th day after harvest, fruit were treated with 1-MCP at 1 °C for 24 hours. In order to evaluate the effect of temperature, apricots were exposed to 1-MCP at 1, 10, and 20 °C (on the 1 st day after harvest). 1-MCP application reduced the ethylene and CO 2 production and delayed softening. Fruit treated on the 1 st day after harvest presented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The fourth group (the control group) was not treated with 1-MCP. Treatment was carried out using the method by Nguyen et al (2016) with slight modifications. The 1-MCP treatments were carried out for 20 hr at 20°C in a gas-tight container with a volume of 1 m 3 .…”
Section: Plant Materials and Sample Treatmentmentioning
confidence: 99%
“…The fourth group (the control group) was not treated with 1-MCP. Treatment was carried out using the method by Nguyen et al (2016) with slight modifications. The 1-MCP treatments were carried out for 20 hr at 20°C in a gas-tight container with a volume of 1 m 3 .…”
Section: Plant Materials and Sample Treatmentmentioning
confidence: 99%
“…Novel postharvest technologies (i.e., the use of ethylene binding packaging materials, or ethylene scavenging agents) could serve effectively for these purposes. 1-MCP (1-methyl-cyclopropene) application as a novel postharvest treatment (Blankenship & Dole, 2003) is proved to be effective against undesired postharvest ripening of several fruits such as apples, bananas, pears, plums, melons (Bagnato et al, 2003;Nguyen et al, 2016;Nguyen et al, 2018;Watkins, 2006), but the possible application for vegetables, especially for broccoli is rather rare lately (Fan & Mattheis, 2000;Fern andez-L eon et al, 2013;Sabir, 2012;Toivonen & DeEll, 1998;Yuan et al, 2010). The main effect of 1-MCP is that this highly active and harmless compound is able to fit in, bind more strongly and block the ethylene receptors than ethylene, thus prolonging storage life (especially if used parallel to cold and/or controlled atmosphere storage), preventing ethylene-dependent physiological responses and providing better retail quality.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological stage of fruit at the time of 1-MCP treatment decides the efficacy of 1-MCP in prolonging the fruit quality [11]. Regarding delayed 1-MCP treatment, previous reports also indicated that the earlier-applied treatments increased the possible storage period [6,10,26].…”
Section: Discussionmentioning
confidence: 99%